The Impact of the Epidemiological Investigation of the Cholera Microbe in Water - M.Turki, Yousef.; M.Alotaibi, Faisal.; Alsubhe, Khalid.A.; Alasmri, Mohammad.A.; Alhothail, Fahad.S.; Alsufi, Abdullah.M.; Alharbi, Hajer.G.; Algethami, Khalid.A.; Alahmari, Eman.M.; Algurashi, Abdulrahman.M. (Journal of Posthumanism, 2024)
Because of its high mortality and morbidity rates, cholera remains a serious danger to worldwide public health. Studies suggest that between 1.3 and 4.0 million cholera cases and 21,000 to 143,000 cholera-related fatalities occur year, an underestimation of the worldwide cholera burden due to variables like inadequate reporting, limited epidemiological surveillance, and a lack of laboratory capacity. Present study evaluates the conditions and scenario in terms of selected cities of Saudi Arabia. Mainly the components are related to secondary data and some of the related items were taken in terms of primary data; as the values are taken from ongoing studies and testing labs. The studies are considered from 1995 to 2019.